High Performance Computing in Science and Engineering’ 04: Transactions of the High Performance Computing Center Stuttgart (HLRS) 2004 - Krause, Egon; Jäger, Willi; Resch, Michael (SpringerLink Bücher, 2005)
Physics -- Chain Conformations and Phase Behavior in Confined Polymer Blends -- Thermal Quark Anti-quark Free Energies, Energies and Screening in Hot SU(3) Gauge Theory -- Simulations of Particle Suspensions at the Institut für Computerphysik -- Numerical Modelling of Convection and Dynamo Processes in Fully Convective Stars -- Large Scale Simulation of a Cooled, Pulsed Jet in Symbiotic Stars -- Image States on the LiF(001)-(1×1) Insulator Surface -- Interaction of Jets with Galactic Winds -- Solid State Physics -- Numerical Studies of Model Colloids and Nano-Wires -- Ab Initio Simulation of Clusters: Relativistic Effects in Structure and Bonding of Noble Metal Nanoparticles -- The Mixed Akali Effect in Ternary Alkali Silicate Melts: Insight from Molecular Dynamics Computer simulations -- Methylchloride Adsorption on Si(001) — Electronic Properties -- Dynamics and Criticality of Correlated Electrons and Quantum Gases -- Electron-doping Evolution of the Quasiparticle Band of the Cuprates -- Computational Fluid Dynamics -- Investigation of Hypersonic Flat-plate Boundary-layer Transition by Direct Numerical Simulation -- DNS Study of spatial discrete suction for Laminar Flow Control -- LES of Shock Wave/Turbulent Boundary Layer Interaction -- Large-eddy Simulation of Incompressible Flow Around a Sphere with Trip Wire at Re = 50 000 -- LES of Passive Heat Transfer in a Turbine Cascade -- Enhanced Mixing in Supersonic Combustion -- Numerical Study of the Influence of Dynamic Pressure and Deflected Ailerons on the Deformation of a High Speed Wing Model -- Numerical High Lift Research II/III -- Numerical Simulation of Electrostatic Spray-painting Processes in the Automotive Industry -- Combination of Detailed CFD Simulations Using the Lattice Boltzmann Method and Experimental Measurements Using the NMR/MRI Technique -- Recent Improvements of the Parallel-Multiblock URANUS 3D Nonequilibrium Code -- Chemistry -- The Iron(III) Catalyzed Michael Reaction — Reactivity Differences Between Several Different Acceptors -- Potential Energy Surfaces of Unusual Double Proton Transfer Reactions -- Quantum Reactive Scattering for Ion-neutral Collisions: The H 3 ? -system -- Glycine at the Water / Pyrite Interface Under Extreme Pressure / Temperature Conditions -- Computer Science -- Performance Analysis of NEC Computers by Using the PARbench Benchmark System -- SKaMPI — Towards Version 5 -- Earth Sciences -- Numerical Considerations of Fluid Effects on Wave Propagation -- Toward a Thermochemical Model of the Evolution of the Earth’s Mantle.